Influences of Seasoned Equity Offerings on Stock Return of Ho Chi Minh Market - Tien, Ho Viet; Ha, Dinh Thi Thu (The Indonesian Capital Market Review, 2013)
This paper investigated the impact of seasoned equity offerings (SEO) on stock return of listed companies in Ho Chi Minh City market using the method “event study” which has been basically formed by Campbell, Lo, and MacKinlay (1997). The sample includes 332 SEOs from 2007 to 2010. The main findings show evidence that the Ho Chi Minh City market was not efficient in terms of the semi-strong form because the price has increased significantly on the ex-right date, day 0. In an opposite way, the market also reacted significantly negatively from T-4 to T-2. There are some significant impacts of timing on issue methods – equity right issues were in priority for favorable time and issues as “dividend by stocks” were chosen during unfavorable time.